Bilingualism and its impact on translation quality in Singapore - Ang, Ching Hoon (2017)
In Singapore, misinterpretations leading to mistranslations happen often in official publications, sparking discussions pertaining to the vetting process of these translations and how they can be managed and prevented. This study seeks to examine the decline in bilingual ability in Singapore and its corresponding effects on translation quality. There are three research questions in this project. (1) How does the language education policy impact bilingualism in Singapore? (2) How does Chinese language proficiency level impact translation quality in Singapore? (3) How would elevating the socio-economic status of the Chinese language in Singapore improve the level of proficiency and the translation quality? These issues are analysed using the results of a questionnaire that was administered on professional translators and translation students. The results from this study will reinforce that it is crucial to raise the profile of the Chinese language by expanding its presence in everyday use among Singaporeans.